2011
DOI: 10.3329/jname.v7i2.5662
|View full text |Cite
|
Sign up to set email alerts
|

Induced magnetic field with radiating fluid over a porous vertical plate: analytical study

Abstract: Abstract:The objective of this investigation is to study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…For program code validation, the author compared the present numerical results with analytical results of Prakash et al (2014), Raptis et al (2003) and Ahmed (2010) in tables 2, 3 and 4 respectively which are available in literature. From these tables, the author observed that the results are in good agreement with their study.…”
Section: Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…For program code validation, the author compared the present numerical results with analytical results of Prakash et al (2014), Raptis et al (2003) and Ahmed (2010) in tables 2, 3 and 4 respectively which are available in literature. From these tables, the author observed that the results are in good agreement with their study.…”
Section: Code Validationmentioning
confidence: 99%
“…Raptis et al (2003) studied the effect of radiation in an optically thin gray gas flowing past a vertical infinite plate in the presence of a magnetic field. Ahmed (2010) found the analytical solutions of induced magnetic field with radiating fluid over a porous vertical plate using Perturbation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal diffusion and natural convection between inclined plates in a porous medium with MHD was analyzed by Raju et al [6]. Ahmed [7] discovered the radiating fluid and an induced magnetic field over a porous vertical plate. Samira et al [8] derived free convection MHD flow of an elastoviscous fluid past an infinite vertical plate.…”
Section: Introductionmentioning
confidence: 99%
“…Orhan and Ahmad [31] examined MHD mixed convective heat transfer along a permeable vertical infinite plate in the presence of radiation and solutions are derived using Kellar box scheme and accurate finite-difference scheme. Ahmed [32] investigated the study of influence of thermal radiation and magnetic Prandtl number on the steady MHD heat and mass transfer mixed convection flow of a viscous, incompressible, electrically-conducting Newtonian fluid over a vertical porous plate with induced magnetic field. When heat and mass transfer occur simultaneously in moving fluid, the relations between the fluxes and the driving potentials are of a more intricate nature.…”
Section: Introductionmentioning
confidence: 99%